2012
DOI: 10.1111/cdev.12021
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Concerns and Expectations as Explanations for Gendered Socialization in African American Families

Abstract: Discrimination concerns and parental expectations were examined as mediators of the relations between gender and parenting practices among 796 African American mothers of 11- to 14-year-olds from the Maryland Adolescent Development in Context Study. Mothers of sons had more concerns about racial discrimination impacting their adolescents' future, whereas mothers of daughters had more gender discrimination concerns. Racial discrimination concerns, but not gender discrimination concerns, were related to lower ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 87 publications
2
51
1
Order By: Relevance
“…In addition, Goff, Jackson, Di Leone, Culotta, and DiTomasso () found that Black boys at 10 years of age were deemed less innocent than their White peers, particularly in a justice system context. Mothers' concerns were also consistent with quantitative research in which Black mothers expressed concern that their sons would experience racial discrimination in school (Varner & Mandara, ) and work finding that Black parents are more likely to talk to their sons about racial discrimination and bias (Bowman & Howard, ).…”
Section: Resultssupporting
confidence: 75%
“…In addition, Goff, Jackson, Di Leone, Culotta, and DiTomasso () found that Black boys at 10 years of age were deemed less innocent than their White peers, particularly in a justice system context. Mothers' concerns were also consistent with quantitative research in which Black mothers expressed concern that their sons would experience racial discrimination in school (Varner & Mandara, ) and work finding that Black parents are more likely to talk to their sons about racial discrimination and bias (Bowman & Howard, ).…”
Section: Resultssupporting
confidence: 75%
“…In addition to behavioral messages, racial barrier messages also mediated the positive association between discrimination and centrality for girls. This finding highlights how gender may influence how parents respond differently to boys' and girls' discrimination experiences (Brown, Tanner-Smith, Lesane-Brown, & Ezell, 2007;Varner & Mandara, 2013). It is interesting that racial barrier messages did not mediate associations with centrality for boys, although they reported more frequent discrimination and racial barrier socialization than girls.…”
Section: Racial Discrimination Racial Socialization and Racial Idenmentioning
confidence: 87%
“…These studies have shown that African American mothers are more emotionally responsive to girls, monitor girls more, enforce more rules directed at girls' behavior, and have higher educational and career expectations for girls (Mandara et al 2012;Mandara 2013a, 2013b). On the other hand, mothers report more conflict with boys than girls (Varner and Mandara 2013a).…”
Section: Gender Differences In Parental Involvement In Educationmentioning
confidence: 96%